2015
DOI: 10.1183/23120541.00044-2015
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled breath hydrogen cyanide as a marker of earlyPseudomonas aeruginosainfection in children with cystic fibrosis

Abstract: Hydrogen cyanide is readily detected in the headspace above Pseudomonas aeruginosa cultures and in the breath of cystic fibrosis (CF) patients with chronic (P. aeruginosa) infection. We investigated if exhaled breath HCN is an early marker of P. aeruginosa infection.233 children with CF who were free from P. aeruginosa infection were followed for 2 years. Their median (interquartile range) age was 8.0 (5.0–12.2) years. At each study visit, an exhaled breath sample was collected for hydrogen cyanide analysis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 28 publications
2
41
0
Order By: Relevance
“…Most recently, a multi-centre study involving 8 UK hospitals has quantified HCN in the exhaled breath of 233 children with CF and demonstrates that HCN is indeed a discreet specific (albeit not yet entirely sensitive) biomarker of PA. The exciting results of this SPACE study are reported recently in ERJ Open Research [10].…”
Section: Introductionmentioning
confidence: 81%
“…Most recently, a multi-centre study involving 8 UK hospitals has quantified HCN in the exhaled breath of 233 children with CF and demonstrates that HCN is indeed a discreet specific (albeit not yet entirely sensitive) biomarker of PA. The exciting results of this SPACE study are reported recently in ERJ Open Research [10].…”
Section: Introductionmentioning
confidence: 81%
“…The technique was employed in the study by Enderby et al 2,. where median values of 13.5 ppb HCN were detected directly in the breath of CF children with a newly discovered P. aeruginosa lung colonization2, whereas in the more recent study by Gilchrist et al 10,. HCN concentrations at or below 7.5 ppb were detected from breath samples collected in bags and measured within 24 hours10.…”
mentioning
confidence: 91%
“…where median values of 13.5 ppb HCN were detected directly in the breath of CF children with a newly discovered P. aeruginosa lung colonization2, whereas in the more recent study by Gilchrist et al 10,. HCN concentrations at or below 7.5 ppb were detected from breath samples collected in bags and measured within 24 hours10. An optimal sensor would be a cheap and simple point-of-care device, allowing for measurements to be carried out directly on human breath, without pre-handling of the samples.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…HCN is considered a potential P. aeruginosa biomarker, and it was detected at median values of 13.5 ppb in children's breath using selected ion flow tube mass spectroscopy (SIFT-MS) 4 . In the SPACE study, Gilchrist and co-workers measured HCN in exhaled breath of CF children, also using SIFT-MS 6 . At present time, SIFT-MS has not been optimized to meet the need for fast detection of bacteria, and the measurements were made after up to 24 hours, whereby some of the exhaled HCN may have been lost.…”
Section: Introductionmentioning
confidence: 99%